Rāsalīlā tathā rāsānukaraṇa vikāsa - Yāmadagni, Vasanta, 1932- (Saṅgīta Nāṭaka Akādemī, 1980)
Study on the philosophical background of Rāsalīlā, dance of Krishna with milk maids, and its impact on the Indian folk dance.